PENGARUH PENGETAHUAN AKUNTANSI, LATAR BELAKANG PENDIDIKAN DAN MOTIVASI KERJA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA PEDAGANG KAKI LIMA DI ALUN ALUN SELATAN YOGYAKARTA - KuntariBudiyati; Hasanah Setyowati (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to analyze the influence of accounting knowledge, educational background, and work motivation on the utilization of accounting information among street vendors in Alun-alun Selatan, Yogyakarta. In the current era of rapid technological advancement, understanding and applying accounting information is crucial for business success, even for small enterprises like street vendors. The research employs a quantitative approach, collecting data through questionnaires distributed to 55 vendors selected using the Slovin formula. The findings reveal that educational background significantly impacts the use of accounting information, with vendors possessing higher educational levels tending to manage financial information more effectively. In contrast, accounting knowledge and work motivation do not show a significant relationship with the utilization of accounting information. This highlights the importance of enhancing financial literacy among street vendors. The study provides recommendations for training programs aimed at improving their financial management skills, ultimately contributing to their business success and supporting the local economy’s growt